Psychiatric treatment preferences of sports psychiatrists for athlete-patients across competitive levels: a 2024 update - Reardon, C. L.; Claussen, M. C.; Creado, S.; Currie, A.; Edwards, C. D. (The Physician and Sportsmedicine, 2025)
Objectives Only two small, prior studies ascertained psychiatric treatment preferences for athletes among sports psychiatrists. This study aims to build upon and update those results by describing comprehensive psychiatric treatment preferences and rationales for those preferences, across competitive levels of athletes, among practicing sports psychiatrists.